An efficient alert system for improving crosswalks’ security - Branquinho, João Tiago Cruz (2019)
A key characteristic of Smart Cities is the ability to reduce conflicts between different agents coexisting in a dynamic system, such as the interaction between vehicles and pedestrians. This dissertation describes a system to augment the awareness of vehicle drivers regarding the presence of pedestrians in nearby crosswalks. To address this need, the system interconnects Road Side Units (RSUs), which are informed about the state of the crosswalks, and vehicles, in order to spread to vehicles the information about the presence of pedestrians in crosswalks. To prevent false information spreading, RSUs sign the alert messages they broadcast and all vehicles can validate the signatures. This poses strong security requirements, such as non-repudiation of alert messages, as well as strong real-time requirements, such as minimum message validation delays among vehicles approaching a crosswalk of interest. Because of this, the system minimizes the usage of asymmetric ciphers, which are fundamental to assure non-repudiation but increase performance penalties, and uses mostly symmetric ciphers for source authentication. To do so, we designed a new protocol, called Nimble Asymmetric Cryptography (NAC), which broadcasts and authenticates, implicit hash messages.